Hubungan Karakteristik Perawat terhadap Pelaksanaan Sasaran Keselamatan Pasien Pasca Akreditasi Rumah Sakit “X” di Kota Palembang Tahun 2018 - Raden Surahmat; Meri Neherta; Nurariati Nurariati (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Safety of patients, nurses, companions and visitors is the main priority of nursing services in hospitals, because quality services will have an impact on hospital accreditation assessments. This study aims to determine the relationship between the characteristics of nurses on the implementation of patient safety goals after accreditation of "X" hospital in the city of Palembang in 2018. This research is descriptive using quantitative methods with sampling techniques using purposive sampling consisting of 96 nurses in 10 wards inpatient "X" Hospital in Palembang city. The study was conducted from March 27 2018 to April 21 2018 using a questionnaire and was analyzed using a computer system. Based on the results of the study, it is known that the characteristics of 96 respondents with vocational education 97.9%, female sex 88.6%, age <35 years 51.1%, working period> 2 years 93.2%, and the implementation of patient safety goals 84 , 1% with details of good identification accuracy 70.8%, good effective communication 94.8%, good drug safety 76.0%, right procedure, location of patients operating both 87.5%, reduction in infection risk both 50.0% and reduction in risk of patients falling well 51.0%. While the results of the analysis used chi square, there was no relationship of gender, age and length of work to the implementation of patient safety goals after hospital accreditation. The implementation of patient safety goals must be carried out by all nurses in the hospital. It is expected that the hospital to build awareness of the importance of patient safety by supporting nurses in integrating activities oriented to patient safety by applying reporting systems, communicating, learning from experience and always prioritizing prevention of risks that will occur in order to improve quality services.